Low-Light Image Enhancement Based on Guided Image Filtering in Gradient Domain - Xiankun Sun; Huijie Liu; Shiqian Wu; Zhijun Fang; Chengfan Li; Jingyuan Yin (International Journal of Digital Multimedia Broadcasting)
We propose a novel approach for low-light image enhancement. Based on illumination-reflection model, the guided image filter is employed to extract the illumination component of the underlying image. Afterwards, we obtain the reflection component and enhance it by nonlinear functions, sigmoid and gamma, respectively. We use the first-order edge-aware constraint in the gradient domain to achieve good edge preserving features of enhanced images and to eliminate halo artefact effectively. Moreover, the resulting images have high contrast and ample details due to the enhanced illumination and reflection component. We evaluate our method by operating on a large amount of low-light images, with comparison with other popular methods. The experimental results show that our approach outperforms the others in terms of visual perception and objective evaluation.